2013
DOI: 10.3109/08820538.2013.771198
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Educational Interventions to Improve Glaucoma Medication Adherence

Abstract: Adherence to prescribed glaucoma medications is often poor, and proper adherence can be challenging for patients. We systematically reviewed the literature and identified eight studies using educational interventions to improve glaucoma medication adherence. Overall, five of the eight studies found that educational interventions lead to a significant improvement in medication adherence, and the remaining studies found a trend towards improvement. Using information from this systematic review and Health Behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 37 publications
2
40
0
4
Order By: Relevance
“…“glaucoma” AND (“patient acceptance of healthcare,” OR “patient compliance,” OR “treatment refusal,” OR “self-efficacy,” OR “self-care,” OR “compliance,” OR “adherence,” OR “persistence,” OR “self-management.”) (Search strategy available online, Appendix 1). 10 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…“glaucoma” AND (“patient acceptance of healthcare,” OR “patient compliance,” OR “treatment refusal,” OR “self-efficacy,” OR “self-care,” OR “compliance,” OR “adherence,” OR “persistence,” OR “self-management.”) (Search strategy available online, Appendix 1). 10 …”
Section: Methodsmentioning
confidence: 99%
“…We identified that successful programs were likely to include in-person counseling to collaborate to overcome patient's barriers to optimal adherence. 10 In 2013, a Cochrane review was published evaluating all interventions whose purpose was to improve glaucoma medication adherence. They included randomized controlled trials (RCTs) of interventions ranging from education and counseling to simplified medication regimens to reminder devices.…”
Section: Introductionmentioning
confidence: 99%
“…19 This builds on a significant body of evidence demonstrating the benefits of interventions that ‘tailor’ health messages 20 by individualizing the “information and behavior change strategies to reach each person based on characteristics unique to that person.” 21 Computer software can tailor the content each individual receives based on personal data like socio-demographic characteristics, health condition, electronic health record data, and survey responses. Tailored educational content can be delivered through a variety of methods: in a web-based module, in print or in-person.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of medication and counseling to support smoking cessation. In a large prospective, randomized, double-blind, active-and placebo-controlled pharmacotherapy trial which evaluated the neuropsychiatric safety and efficacy of varenicline, bupropion, and nicotine replacement therapy (NRT) patch, versus placebo, varenicline showed superior efficacy to placebo (p <0.0001) and both bupropion and NRT patch (p <0.0001) at the end of treatment (weeks 9 through 12) and follow-up (weeks [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Bupropion showed similar efficacy to NRT patch (p=0.6002) and both showed superior efficacy versus placebo (p <0.0001).…”
Section: Introductionmentioning
confidence: 99%
“…Patient educational programs have proliferated to provide health and wellness support through tools such as apps and including a focus on improving adherence to medications [13][14][15][16][17][18]. High levels of medication adherence are associated with better clinical outcomes, greater treatment satisfaction, better quality of life, and lower overall health care costs [19].…”
mentioning
confidence: 99%